The Role of Specialisation in the Export Success of Polish Counties in 2004-2015 - Jarosław M. Nazarczuk; Stanisław Umiński; Krystyna Gawlikowska-Hueckel (Entrepreneurial Business and Economics Review, 2018)
Objective: The objective of this article is to evaluate the role of specialisation in the export success of counties (powiats) (LAU 1) in Poland between 2004 and 2015.